What’s new about symptomatic reflux disease - Solecki, Michał; Wallner, Grzegorz; Masiak, Wioletta; Ćwik, Grzegorz (Polish Journal of Public Health, 2015)
During the last 4 decades reflux disease (GERD) has evolved from being a rare clinical problem to a disease with high incidence. This automatically rises its social costs. First descriptions came from western countries only but nowadays there are many published papers from Asia and Middle East that can be found on the Internet. There is no clear explanation for this fact. Our understanding of GERD has changed over the time. At first GERD, hiatal hernia and oesophagitis were synonyms. Since the 1940s when the first manometrical studies were done it was concerned as lower oesophageal sphincter or peristaltic disfunction. The following years gave a definition of acid-peptic disorder. Nowadays all this concepts are mixed together and we are considering GERD as a heterogeneous clinical problem. In this paper we would like to present up-to-date knowledge about GERD.